Antibacterial and antibiofilm activities of docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) against periodontopathic bacteria. (October 2016) - Sun, Mengjun; Zhou, Zichao; Dong, Jiachen; Zhang, Jichun; Xia, Yiru; Shu, Rong
Abstract: Docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA) are two major omega-3 polyunsaturated fatty acids (n-3 PUFAs) with antimicrobial properties. In this study, we evaluated the potential antibacterial and antibiofilm activities of DHA and EPA against two periodontal pathogens, Porphyromonas gingivalis ( P. gingivalis ) and Fusobacterium nucleatum ( F. nucleatum ). MTT assay showed that DHA and EPA still exhibited no cytotoxicity to human oral tissue cells when the concentration came to 100 μM and 200 μM, respectively. Against P. gingivalis, DHA and EPA showed the same minimum inhibitory concentration (MIC) of 12.5 μM, and a respective minimum bactericidal concentration (MBC) of 12.5 μM and 25 μM. However, the MIC and MBC values of DHA or EPA against F. nucleatum were both greater than 100 μM. For early-stage bacteria, DHA or EPA displayed complete inhibition on the planktonic growth and biofilm formation of P. gingivalis from the lowest concentration of 12.5 μM. And the planktonic growth of F. nucleatum was slightly but not completely inhibited by DHA or EPA even at the concentration of 100 μM, however, the biofilm formation of F. nucleatum at 24 h was significantly restrained by 100 μM EPA. For exponential-phase bacteria, 100 μM DHA or EPA completely killed P. gingivalis and significantly decreased the viable counts of F. nucleatum . Meanwhile, the morphology of P. gingivalis was apparently damaged, and the virulence factor gene expression of P. gingivalis and F. nucleatum was strongly downregulated. Besides, the viability and the thickness of mature P. gingivalis biofilm, together with the viability of mature F. nucleatum biofilm were both significantly decreased in the presence of 100 μM DHA or EPA. In conclusion, DHA and EPA possessed antibacterial activities against planktonic and biofilm forms of periodontal pathogens, which suggested that DHA and EPA might be potentially supplementary therapeutic agents for prevention and treatment of periodontal diseases. Highlights: DHA and EPA showed inhibition on planktonic and biofilm growing P. gingivalis and F. nucleatum. DHA and EPA damaged the bacterial plasma membrane of P. gingivalis. DHA and EPA decreased the virulence factor gene expression of P. gingivalis and F. nucleatum.